OBMEP AS AN INSTRUMENT FOR PROMOTING MATHEMATICS LEARNING: EVIDENCE FROM A PREPARATORY COURSE (REMUNOM, 2026)
This study aimed to investigate the contributions of a preparatory course for the Brazilian Mathematics Olympiad for Public and Private Schools (OBMEP) to the mathematical education of middle school students in the public school system of São Raimundo Nonato – PI. The research adopted a mixed-methods approach, predominantly qualitative, developed from an action-research perspective. Thirty students qualified for the second phase of the OBMEP participated, 15 from level 1 (6th and 7th grades) and 15 from level 2 (8th and 9th grades). Data collection instruments included five discursive simulations, a perception questionnaire, and systematic observations throughout the course. The results showed a gradual improvement in student performance, observed in the average percentage of correct answers in the simulations. The analysis by subject area indicated better performance in arithmetic and logical reasoning, while difficulties persisted in geometry and counting/probability. Beyond the quantitative advances, the qualitative data revealed an increase in interest, motivation, and self-confidence in relation to mathematics. The methodology adopted—based on problem-solving, dialogic classes, individualized monitoring, and the use of organized materials—was identified by students as a determining factor in learning. It is concluded that the preparatory course proved to be a pedagogical strategy, contributing to the strengthening of mathematical skills and the construction of a more positive relationship with the subject, reinforcing the role of OBMEP (Brazilian Mathematical Olympiad for Public Schools).